STRATEGI MUSYRIFAH DALAM PEMBINAAN SANTRI UNGGULAN BERBASIS MANAJEMEN PENDIDIKAN PESANTREN DI PONDOK PESANTREN HAMALARUL QUR`AN KARAWANG - Karina Dhisty Fitria; Diningrum Citraningsih (MPI STAI Sangatta Kutai Timur, 2026)
This study aims to analyze the strategies employed by female supervisors to guide students to become high achievers at the Hamalatul Qur’an Islamic Boarding School in Karawang. The study employs a qualitative approach with a descriptive design. The research subjects include female supervisors, students, and boarding school administrators selected through purposive sampling. Data collection techniques included interviews, observations, and documentation, while data analysis used the Miles and Huberman interactive model, which includes data condensation, data presentation, and conclusion drawing. The results of the study indicate that the female supervisors’ strategies are implemented comprehensively through three main aspects. First, character development through setting a good example, fostering habits, and enforcing discipline. Second, academic development through monitoring learning, providing motivation, and offering support to students facing difficulties. Third, Quran memorization development through the recitation system, review sessions, and the talaqqi method. The success of this strategy is supported by the musyrifah’s commitment, the religious environment of the pesantren, and the support of caregivers and parents, while the challenges faced include differences in students’ personalities and limited time for guidance. Thus, the musyrifah’s strategy plays a significant role in shaping outstanding students.